Pathogenetic, Prognostic, and Therapeutic Role of Fatty Acid Synthase in Human Hepatocellular Carcinoma - Che, Li; Paliogiannis, Panagiotis; Cigliano, Antonio; Pilo, Maria G.; Chen, Xin; Calvisi, Diego F. (Frontiers in Oncology, 2019)
Hepatocellular carcinoma (HCC) is one of the most common solid tumors worldwide, characterized by clinical aggressiveness, resistance to conventional chemotherapy, and high lethality. Consequently, there is an urgent need to better delineate the molecular pathogenesis of HCC to develop new preventive and therapeutic strategies against this deadly disease. Noticeably, emerging evidence indicates that proteins involved in lipid biosynthesis are important mediators along the development and progression of HCC in humans and rodents. Here, we provide a comprehensive overview of: a) The pathogenetic relevance of lipogenic proteins involved in liver carcinogenesis, with a special emphasis on the master fatty acid regulator, fatty acid synthase (FASN); b) The molecular mechanisms responsible for unrestrained activation of FASN and related fatty acid biosynthesis in HCC; c) The findings in experimental mouse models of liver cancer and their possible clinical implications; 4) The existing potential therapies targeting FASN. A consistent body of data indicates that elevated levels of lipogenic proteins, including FASN, characterize human hepatocarcinogenesis and are predictive of poor prognosis of HCC patients. Pharmacological or genetic blockade of FASN is highly detrimental for the growth of HCC cells in both in vitro and in vivo models. In conclusion, FASN is involved in the molecular pathogenesis of HCC, where it plays a pivotal role both in tumor onset and progression. Thus, targeted inhibition of FASN and related lipogenesis could be a potentially relevant treatment for human HCC.